The problems of junior high school students - Nurhasanah, Nurhasanah; Farozin, Muh (COUNS-EDU: The International Journal of Counseling and Education, 2019)
Problem is a state that is not in line with expectations and must be solved immediately. The junior high school student is in the early adolescent phase, which finds many major changes in him that can cause problems. Guidance and conseling services should be provided in accordance with the problems experienced by students and their needs. However, guidance and conseling teachers have difficulty identifying the problems that affect the giving of guidance and counseling services. This study observes the problems experienced by students in junior high school with the number of respondents as many as 193 students. They are first year students of junior high school in Yogyakarta. We analyzed student problems using survey methods with problem-based guidance and counseling instrument, namely Alat Ungkap Masalah (AUM) Umum. The results showed that the 3 highest problem experienced by junior high school students in Yogyakarta covered 45% of he Social Relationship, 44% Personality, and Physical Health got 40%.